STUDENTS NUMERICAL LITERACY ABILITY IN PROBLEM BASED LEARNING WITH ETHNOMATEMATICS NUANCES - Fakhrizal Utama; Zaenuri Zaenuri; Yuli Kurniawati sugiyono Pranoto (Prima: Jurnal Pendidikan Matematika, 2023)
One of the approaches/methods used in learning to improve students' numeracy literacy skills is using Problem Based Learning (PBL). The use of PBL in learning is used for various purposes, starting from increasing mathematical abilities, mathematical communication, and students' numeracy literacy skills. In order for learning to be more meaningful, learning is associated with the culture in the surrounding environment. Ethnomathematics is the term that refers to the combination of culture and mathematics. However, in reality learning mathematics is still centered on the teacher. Innovative learning models are not used by teachers. The purpose of this study was to assess the efficacy of the PBL model with ethnomathematics nuances in improving students' numeracy literacy skills. A quasi-experimental research method was utilized in this study, with one experimental group. As a result, the design employed by the researchers was a one group pretest posttest design. The research sample consisted of 37 students, class IV with saturated sample technique. The type of instrument is a description test. The study's findings demonstrate an improvement and development in the average numeracy literacy skills. Therefore, the application of the PBL model with ethnomathematics nuances can improve students' numeracy literacy skills.